Blendas de polietileno e amido termoplástico modificado - Miranda, Vinícius Atílio Rostelato de (Universidade Federal de São Carlos, 2011)
The development of materials derived from renewable or biodegradable resources has attracted attention from academic and industrial sectors due to the growing need for replacement of synthetic materials derived from renewable sources and also due to the need for biodegradable materials. The interest in the use of blends of thermoplastic starch (TPS) and polyethylene has also gained attention in the last decade due to a new concept in which the increase in the content of materials from renewable sources is required and due to recent advances in the thermoplastic starch technology. In this work we studied blends of low density polyethylene (LDPE)/thermoplastic starch (1:1, w / w). In a first step the thermoplastic starch was prepared by processing corn starch and glycerol in the ratio starch/glycerol 70/30 w/w, modified in the presence of 0; 0.5, 1.5, 2.0, 2.5 and 3.0 wt% of citric acid in a single screw extruder, L/D = 40. In a second step the blends of thermoplastic starch and polyethylene (1:1, w/w) were produced using the same extruders. We investigated the effect of starch modification on the morphology and compatibility of polyethylene and TPS. The materials were characterized by scanning electron microscopy (SEM), tensile-stress mechanical testing, dynamic-mechanical thermal analysis (DTMA), high-performance size exclusion chromatography (HPSEC), infrared spectroscopy (FTIR), X-ray diffraction and water absorption experiments. The modification of starch causes a decrease in its molecular weight and hence the melt viscosity. It was observed that the TPS modification causes a better distribution of the dispersed phase of thermoplastic starch in the blend. This improvement was mainly observed for starch modified by adding 1.0% and 1.5% citric acid. The blends have lower moisture absorption and better mechanical properties with respect to the blends produced with unmodified thermoplastic starch.
Keywords: Blendas; Polímeros biodegradáveis; Materiais termoplásticos; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA